2021
DOI: 10.1002/acr.24416
|View full text |Cite
|
Sign up to set email alerts
|

Do Obesity and Overweight Influence Disease Activity Measures in Axial Spondyloarthritis? A Systematic Review and Meta‐Analysis

Abstract: The aim of our systematic review and meta-analysis was to investigate whether overweight/obesity are associated with higher disease activity measures in patients with axial spondyloarthritis (SpA).Methods. MEDLINE, PubMed, and Web of Science were searched using key terms corresponding to population (axial SpA patients), exposure (overweight/obesity), and outcome (Bath Ankylosing Spondylitis Disease Activity Index [BASDAI] and Ankylosing Spondylitis Disease Activity Score [ASDAS]). Predefined inclusion criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Notably, some studies in rheumatoid arthritis suggested that a slight increase in weight may also occur following MD introduction [28]. That being so, a stable BMI has not prejudiced the observed variations of disease activity in this study, which can be attributed to the diet modification [29].…”
Section: Discussionsupporting
confidence: 48%
“…Notably, some studies in rheumatoid arthritis suggested that a slight increase in weight may also occur following MD introduction [28]. That being so, a stable BMI has not prejudiced the observed variations of disease activity in this study, which can be attributed to the diet modification [29].…”
Section: Discussionsupporting
confidence: 48%
“…Lastly, as the evidence within this review was used to formulate the taskforce’s recommendations, an update was not deemed appropriate. However, this means that some relevant papers have been published in the interim between implementing the search strategy and publishing this paper which are not included 434 435…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, visceral fat has been found to be positively associated with BASDAI and pain, body fat percentage with BASDAI (Aydin et al., 2014), and central obesity with BASDAI and radiographic change (Chen et al., 2020). Body mass index (BMI) is positively associated with BASDAI (Lee et al., 2019; Liew et al., 2020; Ortolan et al., 2020), inadequate response to TNFi treatment (Shan & Zhang, 2019; Singh et al., 2018), new syndesmophyte formation, and Modified Stoke ankylosing spondylitis spine score (mSASSS) progression (Bakirci et al., 2020), worse perceptions regarding the benefits of exercise, and enhanced awareness of barriers to exercise (Durcan et al., 2012). The latter is especially problematic, given the benefits of exercise in patients with AS discussed earlier.…”
Section: Methodsmentioning
confidence: 99%